2021
DOI: 10.21037/acs-2021-rp-fs-28
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of the Ross procedure in adults

Abstract: Background: The optimal aortic valve replacement for young and middle-aged adults remains elusive.Although several high-volume international centers and surgeons have demonstrated excellent long-term results with the pulmonary autograft (Ross procedure) in adult patients, current guidelines from the United States do not favor this technique. We evaluated long-term clinical and echocardiographic outcomes of adult patients undergoing the Ross procedure at our center.Methods: A retrospective review of 225 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Long-term survival rates after the Ross procedure have also been encouraging. Long-term outcomes showed 10-year survival rates ranging from 81% to 94%, while 20-year survival rates ranged from 65% to 92% [26]. These results suggest that the Ross procedure can provide durable survival benefits for appropriately selected patients.…”
Section: Analysis Of Short-term and Long-term Survival Ratesmentioning
confidence: 81%
See 1 more Smart Citation
“…Long-term survival rates after the Ross procedure have also been encouraging. Long-term outcomes showed 10-year survival rates ranging from 81% to 94%, while 20-year survival rates ranged from 65% to 92% [26]. These results suggest that the Ross procedure can provide durable survival benefits for appropriately selected patients.…”
Section: Analysis Of Short-term and Long-term Survival Ratesmentioning
confidence: 81%
“…Ryan et al, 2021 n(225) [26] 20 Year Survival 81.3% (74.8-88.3%) Mortality (In-hospital) 0.9% (30 day) 2.2% Pergola et al, n(536) 2020 [18] 15 Year Freedom from all Re-operation 83% Freedom from Autograft reoperation 81% David et al, n(212) 2019 [23] 20 Year Mortality 10.8% Stelzer et al, n(702) 2021 [25] Perioperative Mortality 1% Aboud et al, n(2444) 2021 [28] 25 Year Survival 75.8% Early mortality 1%…”
mentioning
confidence: 99%
“…However, the PARTNER II trial used an earlier generation of balloonexpandable valves, and the PARTNER III trial noted less PVL but BAV patients were excluded. 6 The clinical significance of mild PVL is unclear but its impact may be increased in a younger patient who will have PVL for a longer period of time. An analysis of 17 studies and 181,433 patients found the risk for moderate to severe PVL to be higher in subjects with BAV than in those with tricuspid aortic valve (RR 1.42; 95% CI [1.29-1.58]; p<0.0001).…”
Section: Transcatheter Aortic Valve Replacement In Bicuspid Aortic Va...mentioning
confidence: 99%
“…There are also data to suggest that the patient's life expectancy is restored to that of a matched group without aortic stenosis. 6 The use of SURD in BAV has been traditionally considered as contraindicated. However, this has been challenged, with multiple groups presenting data showing excellent results in BAV including Sievers type 0 valves.…”
mentioning
confidence: 99%